Why unprecedented ozone loss in the Arctic in 2011? Is it related to climate change? - J.-P. Pommereau; F. Goutail; F. Lefèvre; A. Pazmino; C. Adams; V. Dorokhov; P. Eriksen; R. Kivi; K. Stebel; X. Zhao; M. van Roozendael (Atmospheric Chemistry and Physics, 2013)
An unprecedented ozone loss occurred in the Arctic in spring 2011. The details of the event are revisited from the twice-daily total ozone and NO 2 column measurements of the eight SAOZ/NDACC (Système d'Analyse par Observation Zénithale/Network for Detection of Atmospheric Composition Changes) stations in the Arctic. It is shown that the total ozone depletion in the polar vortex reached 38% (approx. 170 DU) by the end of March, which is larger than the 30% of the previous record in 1996. Aside from the long extension of the cold stratospheric NAT PSC period, the amplitude of the event is shown to be resulting from a record daily total ozone loss rate of 0.7% d −1 after mid-February, never seen before in the Arctic but similar to that observed in the Antarctic over the last 20 yr. This high loss rate is attributed to the absence of NO x in the vortex until the final warming, in contrast to all previous winters where, as shown by the early increase of NO 2 diurnal increase, partial renoxification occurs by import of NO x or HNO 3 from the outside after minor warming episodes, leading to partial chlorine deactivation. The cause of the absence of renoxification and thus of high loss rate, is attributed to a vortex strength similar to that of the Antarctic but never seen before in the Arctic. The total ozone reduction on 20 March was identical to that of the 2002 Antarctic winter, which ended around 20 September, and a 15-day extension of the cold period would have been enough to reach the mean yearly amplitude of the Antarctic ozone hole. However there is no sign of trend since 1994, either in PSC (polar stratospheric cloud) volume (volume of air cold enough to allow formation of PSCs), early winter denitrification, late vortex renoxification, and vortex strength or in total ozone loss. The unprecedented large Arctic ozone loss in 2011 appears to result from an extreme meteorological event and there is no indication of possible strengthening related to climate change.